Synthesis, Biological Evaluation, and Mode of Action of Pulsatilla Saponin D Derivatives as Promising Anticancer Agents - Yuanying Fang; Daoyong Hu; Huilan Li; Huilan Li; Jianguo Hu; Yanhua Liu; Zhifeng Li; Guoliang Xu; Lanying Chen; Yi Jin; Shilin Yang; Zunhua Yang (Frontiers Media S.A., 2019)
A series of ester and amide derivatives of triterpenoid saponin Pulsatilla saponin D (PSD) were designed, synthesized, and evaluated for their antiproliferative activity. Compounds 1 and 6 displayed 1.7-8.3 times more potent cytotoxicity (IC50 = 1.2-4.7 and 1.7-4.5 μM, respectively) against five human tumor cell lines (SMMC-7721, MCF-7, NCI-H460, A549, and HCT-116) in vitro and lower acute toxicity to mice in vivo than did PSD. Furthermore, compound 6 was observed to show potent tumor growth inhibition against mice H22 hepatocellular cells (49.8% at 20 mg/kg) and induce cell cycle at G1 phase and apoptosis in HCT-116 cells.